Modulatory effects of sodium glutamate on functions of rat's circulating phagocytic cells in vivo and in vitro - Rudyk, M.P.; Pozur, V.V.; Opeida, I.V.; Voieikova, D.O.; Khranovska, N.M.; Fedorchuk, O.G.; Berehova, T.V.; Ostapchenko, L.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
The functional state and metabolic patterns of peripheral blood phagocytes from adult male rats, which were injected with sodium glutamate a the dose of 20 mg/animal during the early postnatal period, are inves tigated. For the characteristic of phagocyte functions, their oxidative metabolism and phagocytic activity are analyzed by flow cytometry. The animals treated with sodium glutamate developed obesity in adulthood. The obesity was associated with the pro-inflammatory metabolic profile of circulating granulocytes, as eviden ced by increased oxidative metabolism along with decreased phagocytic activity of these cells. The treatment of peripheral blood phagocytes from adult intact rats with sodium glutamate at concentrations of 20, 2.00, 0.20 and 0.02 mg/ml in vitro caused their antiinflammatory metabolic changes.